2013
DOI: 10.1080/15257770.2013.774012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Clinical Effects ofS-Adenosylmethionine on Mood and Behavior in Lesch-Nyhan Patients

Abstract: Four patients tolerated the drug and reported beneficial effects. The majority experienced worsened behavior. The 2 assessment tools demonstrated effectiveness in quantitatively evaluating the self-injurious behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…A less rigorous but similarly positive description was reported for a young LNS patient shortly thereafter [Dolcetta et al, 2013]. However, Dolcetta et al [2013] conducted a study where SAM was administered to 13 LNS patients; 4 showed significant positive improvement, but the majority of patients experienced worsening of their symptoms. Chen et al [2014] administered SAM to 5 related LNS patients and found a significant reduction of self-harm and aggressive behavior in all 5 patients.…”
Section: Treatment With S-adenylmethioninementioning
confidence: 99%
“…A less rigorous but similarly positive description was reported for a young LNS patient shortly thereafter [Dolcetta et al, 2013]. However, Dolcetta et al [2013] conducted a study where SAM was administered to 13 LNS patients; 4 showed significant positive improvement, but the majority of patients experienced worsening of their symptoms. Chen et al [2014] administered SAM to 5 related LNS patients and found a significant reduction of self-harm and aggressive behavior in all 5 patients.…”
Section: Treatment With S-adenylmethioninementioning
confidence: 99%
“…SAM treatment has previously been reported in only few patients Dolcetta et al 2013;Glick 2006); in some of these, supplementation with SAM led to a drastic reduction in self-mutilation events and very good clinical outcome. This was investigated with (Dolcetta et al 2013) or without Glick 2006) formal assessment tools, and we decided here to base effect on parental judgment and documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Purine depletion in tissue culture models and selective vulnerability of basal ganglia in HPRT-deficient mice was shown in several studies (Dunnett et al 1989;Finger et al 1988;Jinnah et al 1992Jinnah et al , 1994Jinnah et al , 1999, and SAM could act on this by replenishing adenosyl stores in LND. Other authors discuss a role of SAM in neurotransmitter synthesis and metabolism (Dolcetta et al 2013;Miller 2008), but this clearly needs more studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations